2015
DOI: 10.1245/s10434-015-4944-y
|View full text |Cite
|
Sign up to set email alerts
|

Does a Positive Axillary Lymph Node Needle Biopsy Result Predict the Need for an Axillary Lymph Node Dissection in Clinically Node-Negative Breast Cancer Patients in the ACOSOG Z0011 Era?

Abstract: Background ACOSOG Z0011 defined clinical node negativity by physical exam alone. Although axillary US with biopsy has a positive predictive value for lymph node (LN) metastases approaching 100%, it may not appropriately identify clinically node-negative women with ≥3 positive LNs (+LNs) who require ALND. We sought to identify the total number of +LNs in women presenting with cT1-2N0 breast carcinoma with a positive preoperative LN biopsy to evaluate the potential for overtreatment when ALND is performed on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 17 publications
(14 reference statements)
4
38
1
1
Order By: Relevance
“…14 Among 141 of our Z0011-eligible patients with a positive image-guided axillary needle biopsy, 47% had 1–2 positive nodes and could avoid ALND. 7 These data confirm that preoperative axillary imaging and even a positive axillary needle biopsy are inadequate to make the decision for ALND, and that for Z0011-eligible patients, a negative clinical examination of the axilla is sufficient.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…14 Among 141 of our Z0011-eligible patients with a positive image-guided axillary needle biopsy, 47% had 1–2 positive nodes and could avoid ALND. 7 These data confirm that preoperative axillary imaging and even a positive axillary needle biopsy are inadequate to make the decision for ALND, and that for Z0011-eligible patients, a negative clinical examination of the axilla is sufficient.…”
Section: Discussionmentioning
confidence: 58%
“…Patients with cN0 disease but biopsy-proven nodal metastases were managed with SLN biopsy as above, and have been reported previously. 7 Intraoperative SLN frozen section was eliminated, and patients were advised that a second surgery for ALND might be necessary. Management no longer employed the Memorial Sloan Kettering Cancer Center (MSKCC) nomogram to estimate the risk of additional positive nodes after SLNB.…”
Section: Methodsmentioning
confidence: 99%
“…21 However, the role of axillary imaging in cN0 patients meeting ACOSOG Z0011 criteria has been questioned. We have previously demonstrated that the identification of abnormal nodes on preoperative imaging 22 or even a positive needle biopsy 23 does not reliably identify a group of patients who require ALND when ACOSOG Z0011 eligibility criteria are otherwise met. While BMI has been not been shown to impact the sensitivity of axillary ultrasound 24-26 , our data suggest that obesity itself is not an indication for additional axillary evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, axillary ultrasound is used to identify axillary disease in clinically node-negative patients to omit the SLN procedure and proceed directly to axillary dissection. In the ACOSOG Z0011 era, this indication has become controversial inasmuch as patients with a positive preoperative axillary ultrasound may still undergo the SLN procedure without axillary dissection [23.] The results of the following 2 trials have the potential to establish a new indication for axillary ultrasound as a procedure to exclude high-volume axillary disease and spare patients any axillary surgery.…”
Section: Ongoing Randomized Controlled Trialsmentioning
confidence: 99%
“…If post-mastectomy radiotherapy including the regional nodes is indicated according to local protocols due to the positive SLN per se, ALND can be safely omitted, a lesson learned from EORTC AMAROS [12,31.] Finally, potential predictors of high nodal disease volume are sometimes used in clinical practice to indicate ALND; the most common are lymph node metastases detected by imaging before surgery and microscopic extranodal disease in the SLN [32,33,34] While the extent of extracapsular extension may influence the need for ALND [35], a positive imaging-guided axillary lymph node needle biopsy does not accurately predict the need for ALND [23.] BOOG 2013-07 from the Netherlands, SERC/IPC 2012-001 from France and the Alliance trial A011202 may eliminate most of the remaining indications for ALND, potentially leaving only confirmed palpable lymph node metastases as the last absolute indication for ALND in the near future.…”
Section: Current and Future Axillary Treatmentmentioning
confidence: 99%